El derecho penal subterráneo y el microtráfico de sustancias sujetas a fiscalización. - Barahona Caichug, Alex Fabricio (2023)
ABSTRACT: This paper analyzes the problem of micro-trafficking of substances subject to control from a criminological perspective, going through the historical background in which Ecuador has been sentenced internationally, as well as the historical legislation that regulated the trafficking of substances, up to the Comprehensive Organic Criminal Code (COIP) and its eminently punitive perspective that, as we will see later, contravenes the system of guarantees proposed in the Constitution. It also addresses the excessive exercise of constant punitive power in the infra-constitutional norm, the criminalization of poverty through the persecution of micro-trafficking and the gradual disintegration of the guarantee program that tried to create institutions that protect rights and that instead of solving the crisis of our penal system have aggravated it, deeply fracturing the constitutional State that we intend to establish. The COIP establishes an efficient penal program, however, it also hides an uncontrolled and unobjective increase in the quantum of sentences, which, added to civil liability and security measures, aggravates the conditions of the prisoner. To this is added the doctrinal contradictions of the penal system due to its flaws in the very bases of its technical-scientific justification, which has led to the State failing to exercise rational punitive power, since it takes advantage of methods whose legitimacy is doubtful. for the investigation and prosecution of criminally relevant facts. These characteristics constitute in Ecuador what the doctrine has called underground criminal law.